Trophoblast-derived hyaluronan promotes the regulatory phenotype of decidual macrophages. Issue 2 (February 2019) - Wang, Songcun; Sun, Fengrun; Han, Mutian; Liu, Yinghua; Zou, Qinyan; Wang, Fuxin; Tao, Yu; Li, Dajin; Du, Meirong; Li, Hong; Zhu, Rui
Abstract : There is delicate crosstalk between fetus-derived trophoblasts (Tros) and maternal cells during normal pregnancy. Dysfunctions in interaction are highly linked to some pregnancy complications, such as recurrent spontaneous abortion (RSA), pre-eclampsia and fetal growth restriction. Hyaluronan (HA), the most abundant component of extracellular matrix, has been reported to act as both a pro- and an anti-inflammatory molecule. Previously, we reported that HA promotes the invasion and proliferation of Tros by activating PI3K/Akt and MAPK/ERK1/2 signaling pathways. While lower HA secretion by Tros was observed during miscarriages than that during normal pregnancies, in the present study, we further confirmed that higher secretion of HA by Tros could induce M2 polarization of macrophages at the maternal–fetal interface by interacting with CD44 and activating the downstream PI3K/Akt-STAT-3/STAT-6 signaling pathways. Furthermore, HA could restore the production of IL-10 and other normal pregnancy markers by decidual macrophages (dMφs) from RSA. These findings underline the important roles of HA in regulating the function of dMφs and maintaining a normal pregnancy.